The Thai Government and Support for Thai Films in Internati - Tadaamnuaychai, Monrudee (Siam Communication Review, 2023)
The support of government agencies to the Thai film industry has continued from year to year. At present, the integration of relevant government agencies according to the National Film and Video Committee's integrated work plan "Content Thailand" is in response to the national strategy on building competitiveness. and strategy to promote film and video phase 3 (2017-2021) by continuously supporting, disseminating and generating income from Thai film and video industry abroad. The Ministry of Culture has integrated cooperation with the Department of Tourism, Ministry of Tourism and Sports and the Department of International Trade Promotion Ministry of Commerce on behalf of the Thailand team under the name "Content Thailand" to promote Thai movies to foreign film markets. This article aims to share experiences and benefits of receiving government support to attend film festivals abroad. As the author had the opportunity to attend film booths and negotiate trade with foreign buyers with support from government agencies, it was found that there are many advantages, namely, the exhibition booth is in the form of a pavilion with a spacious area attracting the attention of the participants and a lot of visitors and trade negotiations. The Department of International Trade will negotiate the purchase of exhibition space with the organizers, resulting in a good space, spacious and the department will take care of the design. Also the department allocated the number of exhibition booths appropriately and in line with the number of entrepreneurs traveling to the event. This made the booth unique and beautiful. And the Department of International Trade Promotion has purchased public relations media at the event and organized various public relations activities in order to build a good relationship between Thai entrepreneurs and foreign buyers, allowing entrepreneurs to have the opportunity to get to know more buyers and gain more customer databases. In addition, the Department of International Trade Promotion organizes a matching event for entrepreneurs, which provides an opportunity to get to know buyers and have a trade negotiation, which is very beneficial for new entrepreneurs who have just entered. Comes in the industry and doesn't have a buyer database yet.